Hot topics in renal cancer pathology: implications for clinical management. Issue 12 (2nd December 2022) - Cimadamore, Alessia; Caliò, Anna; Marandino, Laura; Marletta, Stefano; Franzese, Carmine; Schips, Luigi; Amparore, Daniele; Bertolo, Riccardo; Muselaers, Stijn; Erdem, Selcuk; Ingels, Alexandre; Pavan, Nicola; et al.
ABSTRACT: Introduction: The updated European Association of Urology (EAU) Guidelines issued a weak recommendation for adjuvant pembrolizumab for patients with high-risk operable clear cell Renal Cell Carcinoma (ccRCC). High risk of recurrence was defined, as per protocol-criteria, as T2 with nuclear grade 4 or sarcomatoid differentiation, T3 or higher, regional lymph node metastasis, or stage M1 with no evidence of disease. Considering the heterogeneous population included in the recommendation, it has been questioned if adjuvant pembrolizumab may lead to overtreatment of some patients as well as undertreatment of patients with worse prognosis. Areas covered: In this review, we discuss the issues related to the assessment of pathological features required to identify those patients harboring a high-risk tumor, highlighting the issue related to interobserver variability and discuss the currently available prognostic scoring systems in ccRCC. Expert opinion: PPathologist assessment of prognostic features suffers from interobserver variability which may depend on gross sampling and the pathologist's expertise. The presence of clear cell feature is not sufficient criteria by itself to define ccRCC since clear cell can be also found in other histotypes. Application of molecular biomarkers may be useful tools in the near future to help clinicians identify patients harboring tumors with worse prognosis.